Mycobiota and mycotoxins of almonds and chestnuts with special reference to aflatoxins - Rodrigues, Paula Cristina Azevedo (2012)
Almond tree, Prunus dulcis, is a cultivated tree originating from wild trees from Central Asia which is currently dispersed throughout the world, mainly in Mediterranean countries and others with similar climatic characteristics, likeUSA. Chestnuts are produced by a wide variety of species fromthe genus Castanea. These species divide into threemajor groups that have specific geographical distribution and produce three varieties of chestnuts: the Asian (Japanese and Chinese) chestnut; the American chestnut; and the European (sweet) chestnut. Studies on mycobiota of almonds and chestnuts make it clear that Aspergillus species are frequent in these commodities, Sections Flavi and Nigri being the predominant aspergilla. Despite of it, the contamination risk with Aspergillus Section Flavi and their mycotoxins, namely aflatoxins, is much more studied than any other. Tree nuts are among the commoditieswith moderate to high risk of aflatoxin contamination, since they are generally produced under environmental conditions which also favour growth of aflatoxigenic fungi and toxin production. In fact, biotic and abiotic conditions underwhich nuts are produced, stored and processed are key factors to the level of fungal and aflatoxin contamination. The aimof this review is to outline the overall aspects underlying fungal andmycotoxin contamination of two of the most important nuts produced worldwide, almonds and chestnuts, with special incidence on aflatoxins and aflatoxigenic fungi.